The empire of gold - Chakraborty, S. A. (Chakraborty, S. A. Daevabad trilogy, 2020)
Nahri and Ali are determined to save both their city and their loved ones, but when Ali seeks support in his mother's homeland, he makes a discovery that threatens not only his relationship with Nahri, but his very faith.